Investigation of aerodynamic effects on the high-speed train exposed to longitudinal and lateral wind velocities. (February 2016) - Yu, Mengge; Liu, Jiali; Liu, Dawei; Chen, Huanming; Zhang, Jiye
Abstract: The wind stability of the high-speed train has gained an increasing interest in the last few years. In this paper, an investigation of the effects of stochastic winds with longitudinal and lateral components on the high-speed train is described. The longitudinal and lateral wind time histories at the position of a moving vehicle, for a variety of wind directions, are first simulated. An algorithm for computing the unsteady aerodynamic load time histories is then derived for a moving vehicle. A typical railway vehicle has been modeled using the vehicle dynamic simulation package 'Simpack', and the unsteady wind loads of the same vehicle are applied to the vehicle model to investigate the dynamic response behavior. The simulated vehicle behavior is assessed against the indicator of load reduction factor, which indicates wheel unloading and therefore potential roll over. The characteristic wind curves (CWC) and its spread range are then obtained to evaluate the operational safety of the high-speed train. The results demonstrate that the operational safety of the high-speed train will be overestimated if the lateral wind velocity is not considered, especially for the small angles between vehicle and wind. Graphical abstract: Highlights: A stochastic wind mode with longitudinal and lateral components is set up. The formula for computing unsteady aerodynamic loads is given for a moving train. The characteristic wind curves (CWC) are given to evaluate the operational safety. Operational safety will be overestimated if the lateral wind velocity is ignored.